Branding Strategy of PDI Perjuangan in Regional Election 2024: A Qualitative Approach - Niazi, Hakam Ali (International Journal of Business Studies, 2024)
Political branding strategies are key in attracting voters' attention and building a strong positive image. Honest and intelligent messages, as well as the use of positive symbolism, are considered effective in building voter trust and support. While social media offers opportunities, challenges in its use remain significant, including how candidates convey messages that are consistent and relevant to voter expectations, as well as the risk of misinformation and fake news that can damage a candidate's image. The research also highlights the importance of a deep understanding of voters' values ​​and expectations in forming an effective branding strategy that is in line with political ideology. This research design uses a qualitative case study approach on the election of the Governor of NTB Province by the PDI Perjuangan. This approach can explore in depth the branding strategies of prospective candidates, political ideology and social media management as a means of promotion and communication. The method applied was in-depth interviews conducted with the NTB Pilkada winning team, consisting of five informants from PDI Perjuangan, conducted in May-June 2024 and visualized using NVIVO software. The results of the interview show that PDI Perjuangan was able to successfully form a personal brand that was relevant to the expectations of the community by implementing a focused and integrated strategy. Through an in-depth approach to political values ​​and candidate vision, PDI Perjuangan can build a strong and trustworthy candidate image in the eyes of voters. The importance of consistency in conveying relevant and authentic messages through various communication platforms, such as social media, direct campaigns and community events, is key in strengthening effective personal branding. Social media management strategies by potential candidates from the PDI Perjuangan are an important key in influencing public opinion and strengthening the support base.